Impaired fasting pyloric compliance in gastroparesis and the therapeutic response to pyloric dilatation. Issue 4 (19th December 2014) - Gourcerol, G.; Tissier, F.; Melchior, C.; Touchais, J. Y.; Huet, E.; Prevost, G.; Leroi, A. M.; Ducrotte, P.
Summary Background Pyloric pressure and compliance have never been investigated in health nor gastroparesis. Aim We hypothesised that pyloric pressure and/or compliance may be altered in gastroparesis. Methods Fasting pyloric pressure and compliance were investigated in 21 healthy volunteers (HV), 27 gastroparetic patients (GP) and 5 patients who had undergone oesophagectomy without pyloroplasty as positive controls. Under videofluoroscopic control, pyloric compliance and pressure were measured by the EndoFLIP technique. Gastric emptying half time (T1/2) using 13C–octanoic acid breath test, as well as symptoms and quality of life (GIQLI score) were also monitored. Results Mean fasting pyloric compliance was measured at 25.2 ± 2.4 mm²/mmHg in HV, and was lower both in GP (16.9 ± 2.1 mm²/mmHg; P < 0.05) and patients with oesophagectomy (10.9 ± 2.9 mm²/mmHg; P < 0.05). By contrast, fasting pyloric pressure was not different among groups. Fasting pyloric compliance and pressure correlated with T1/2 in GP (R = −0.43; P = 0.04). Fasting pyloric compliance, but not pressure, correlated with symptoms and GIQLI score. Pyloric dilation in 10 GP with low fasting pyloric compliance (<10 mm²/mmHg) increased compliance from 7.4 ± 0.4 to 20.1 ± 4.9 mm²/mmHg (P < 0.01) and improved the GIQLI score from 72.5 ± 5.5 to 89.3 ± 6.1 (P = 0.04). Conclusion This prospective study assessed pyloric compliance for the first time, and showed that fasting pyloric compliance is decreased in gastroparetic patients and is associated with T1/2, symptoms and quality of life. This suggests that pyloric compliance may be a new relevant metric in gastroparetic patients, and may be useful to target patients for pyloric dilation or botulinum toxin injection.